As novas tendências pedagógicas e concepções curriculares no currículo do Colégio Antônio Araripe - Silva, Argentina Cardoso e (2015)
This study is an approach on curriculum of a private school with a focus on reality experienced in this school. The theme is basically questions concerning the pedagogical concepts and its manifestation in curriculum design. Aims to describe the curriculum as an area of educational interactions, and a set of teaching guidelines that are articulated to guide the organization and the development of autonomous educational practices aimed at the integral formation of children and young people within the current Curriculum Proposal of Antonio College Araripe. The analysis is guided by the National Curriculum Parameters, from the point of view of historians, laws, experts and their teachers, in order to contribute to teacher training. The methodology used was through a literature search that takes the principles of qualitative approach, understanding that, in the social sciences and dealing specifically with educational phenomena, is identified as unfinished character, with creative dimension, self-forming, and intentionality. We also used observations together teachers and students of the institution for a more accurate basis. Also taking the significant contribution of authors such as Freire, Libâneo, Saviane, Gonzales and others.